Assessment, Evaluation, and Repair of Concrete, Steel, and Offshore Structures - El-Reedy, Mohamed Abdallah; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Due to age and increased loading on buildings, structural assessment and repair is routinely required with accuracy and professionalism. Our target isto have a building durable along its life time. The typical causes of structural failure and their mechanisms will be presented in this book for all types of structure, and further addressed by numerous case studies and engineering calculations. The up-to-date methods for evaluation and assessment the existing structure will be discussed. It will also examine different codes related to structural assessment and will present project management strategies from the feasibility stage through operations and maintenance.
Chapter 1 Cases of Structure Failure Chapter 2 Project Management and Design-Induced Structure Failure Chapter 3 Problems in Quality Management System Chapter 4 Bad Materials Cause Failures Chapter 5 Loads and Structure Failure Chapter 6 Reliability-Based Design for Structures Chapter 7 Reliability of Concrete Structure Exposed to Corrosion Chapter 8 Inspection Methodology: Visual Inspection Chapter 9 Inspection Methods Chapter 10 Repair of Concrete, Steel, and Offshore Structures.
Includes bibliographical references and index.
Also available in print format.
Keywords: Offshore structures -- Maintenance and repair; concrete cracks; concrete structure repair; corrosion; ISO 9001 requirements; load factors; offshore structures; risk assessment; steel structure repair; structural assessment; Electronic books